Allocation of investment lands for BOT projects under Iraqi law: problem and solution - Zghair, Aqeel K.; Abdul Rahman, Rohana; Abdullah, Nor Anita (IJTRD, 2017)
Iraq is a developing country. It is lacking of the vital infrastructure such as water supply, power plant, railways, bridges, sewage and oil and gas transportation networks etc.The governments are unable to start such mega-projects to develop their infrastructure, due to lack of financial resources.To counter the paucity of funds in public sector, many governments have engaged the private sector to meet the increasing demands upon the public services.These public private partnerships have different forms of contracts, the most famous and important is Build-Operate-Transfer (BOT) contract.In developing countries like Iraq these types of contracts can play important role in infrastructure development. But, unfortunately this concept is not very popular in Iraq.For that purpose, this paper is geared toward understanding the legal challenges that impede application of the BOT contracts into Iraq.This paper reviews the most important legal challenge which is the problem of allocation of lands for BOT projects. This study utilized qualitative and descriptive research methods, to describe the problem of allocation of the investment land which impede or obstruct the performance of the BOT contract in Iraq. “Descriptive research is suitable with this study for it describes the state of affairs as it exists at present.Qualitative method is also suitable when there is a need for exploring and understanding the interpretations of individuals or certain groups given to a particular phenomenon or problem”.[1] This study has attempted to interview participants to get their perception on problem of allocation of land as a negative factor prevents the application of BOT contracts in the country.